Effect of Subject Mass with Feedback Linearisation Controller for Induced Sit-to-Stand Regulation - Ahmed, Mohammed; Huq, M. Saif; Ibrahim, Babul S. K. K. (Applications of Modelling and Simulation, 2019)
Presented is the application of the Feedback Linearisation Control (FLC) method for compensation of variations in human masses for the restoration of sit-to-stand movement function with the aid of Functional Electrical Stimulation. According to literature, enhancement of the control system of such arrangements, which is one of the promising techniques employed is required to attain the desired goal. Hence, improving the system by making it more accurate and robust with aim ushering such devices towards clinical acceptance. The FLC approach is employed, and effort is made to investigate the effect of global human mass distribution as obtained in the literature. The plant is modelled by using the Newton-Euler and Euler-Lagrange methods for the segment dynamics, and the muscles model is adopted from the previous works. The plant for the study is the paraplegic subject and for sit-to-stand movement revival. The control system tries to maintain the stimulation current optimum during the entire process. Results show remarkable improvements with a drastic reduction in the stimulation current, the rate of change in the stimulation current, and the tracking error. Therefore, the system would have a drastic enhancement in accuracy and delayed attainment of fatigue.